prove that : tan theta + tan ( π - theta ) + cot ( π/2 + theta ) - tan (2π - theta ) = 0
Please answer this question
Answers
Answered by
3
⇒ tanθ + tan(π - θ) + cot(π/2 + θ) - tan(2π - θ)
⇒ tanθ + (- tanθ) + cot(π/2 - (-θ)) - tan(π - (-π+θ))
⇒ tanθ - tanθ + tan(-θ) - [-tan(-π + θ)]
⇒ tan(-θ) + tan(-(π - θ))
⇒ - tanθ - tan(π - θ)
⇒ - tanθ - [ -tanθ]
⇒ - tanθ + tanθ
⇒ 0
Identities used:
tan(π - A) = - tanA
cot(π/2 - A) = tanA
tan(-A) = - tanA
Answered by
12
⇒ tanθ + tan(π - θ) + cot(π/2 + θ) - tan(2π - θ)
⇒ tanθ + (- tanθ) + cot(π/2 - (-θ)) - tan(π - (-π+θ))
⇒ tanθ - tanθ + tan(-θ) - [-tan(-π + θ)]
⇒ tan(-θ) + tan(-(π - θ))
⇒ - tanθ - tan(π - θ)
⇒ - tanθ - [ -tanθ]
⇒ - tanθ + tanθ
⇒ 0
Similar questions